Development of Spanish villages through oral memory: mid-twentieth century El Campello - Galiana, Mercedes; Conesa, Salvador; Alcaide-Ramírez , Aurora (Journal of Architecture and Urbanism, 2022)
Oral memory is one amongst the most valuable sources of human knowledge, even more so nowadays when the COVID-19 pandemic has taken so many of our elders out. The personal narratives of our towns’ dwellers during the past century let us know not only their way of life, customs, and traditions, but also the morphology of the city, its layout and urban evolution, its architecture –both for family homes and monuments–, and most significant of all, the way of using said spaces. The researchers behind this paper, in partnership with Grup Salpassa and the Council of El Campello, have chosen a methodology based on the oral history to expand the knowledge of the mid-20th century village by means of a series of interviews with some octogenarian locals –shaped as thematic “micro-histories”, published on social media, and orthophotos, which are subject to urban analysis with the location of streets, public buildings, facilities, and commercial areas. All this is accompanied by moving and previously unpublished images of everyday life and festivities, which set up a stronger emotional bond and stronger terrain roots for current societies.